Development and Characterization of Nutmeg Shell-Based Activated Carbon for Ethylene Adsorption in Fruit Storage - Sri Ayu La Aji; Usman Ahmad; Dyah Wulandani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Nutmeg shells are categorized as hardwood containing carbon such as cellulose and lignin, making them ideal for use as a material for producing activated charcoal. Activated charcoal can be used as an additive to absorb ethylene, O₂, CO₂, and H₂O to slow down fruit ripening. This study was conducted to produce and characterize ethylene absorbers made primarily from Fakfak nutmeg shells and to determine the effectiveness of ethylene absorbers in delaying the ripening of climacteric fruits. Ethylene adsorbents were produced using a pyrolysis method followed by chemical activation. Characterization of surface area and functional groups was performed through SEM and BET tests, as well as FT-IR tests. To ensure the effectiveness of the absorption capacity, the chemical-physical properties were characterized in accordance with Standard of Indonesia and gas chromatography. The results of the activated charcoal test showed a change in the surface area from 298.211 m²/g to 335.198 (BET). FT-IR test results showed the formation of functional groups, namely -OH, C=C, CO₂, C-H, and C-O groups. GC test results showed 90.5% ethylene absorption. The application of nutmeg shell adsorbent on bananas using sealed LDPE plastic packaging showed that nutmeg shell adsorbent was able to maintain banana quality up to 15 days, although there was no significant difference between treatments (p > 0.05).